A new species of leaf-litter inhabiting Georissus from Borneo (Coleoptera: Hydrophiloidea: Georissidae) - Fikáček, Martin (Zootaxa, 2012)
Georissus (Neogeorissus) smetanai sp. nov. is described from Mt. Kinabalu National Park, Sabah, Malaysia. Long series of thisspecies has been sifted from cloud forest leaf litter in contrast to most species of the genus, which are most frequently collectedin riparian zones. The species is compared with G. lateralis Delève, 1967 and G. inflatus Delève, 1972, which were collected under similar circumstances and the leaf-litter habits of the three species are briefly discussed.Keywords. Georissus, new species, leaf litter, terrestrial habitats, aptery, Malaysia, Borneo, Sri Lanka, Republic of the Congo